CaWO4 crystals as scintillators for cryogenic dark matter search - Ninkovic, J; Angloher, G; Bucci, C; Cozzini, C; Frank, T; Hauff, D; Kraus, H; Majorovits, B; Mikhailik, V; Petricca, F; Probst, F; Ramachers, Y; et al. (2005)
Although it is well known that CaWO4 is a scintillator it is not often used. mainly because it has a slow light response. However, a high Z and a good light output make this crystal a candidate for use in direct dark matter search experiments. The Cryogenic Rare Event Search using Superconducting Thermometers (CRESST II) experiment looks. for hypothetical massive elementary particles called Weakly Interacting Massive Particles (WIMPs). In an elastic collision of WIMPs with ordinary matter a WIMP transfers part of its energy to a nucleus. Such nuclear recoils are the signals dark matter searches look for. CRESST is using CaWO4 crystals with coincident detection of phonons and scintillation light to suppress radioactive background. Light output and energy resolution of different CaWO4 samples were systematically measured. Best samples have an energy resolution at the Cs-137; line (661 keV) < 8%. As CRESST is a rare event search experiment it has to prevent the background caused by natural radioactivity; therefore, a study of the radiopurity of CaWO4 crystals has been performed. X-ray luminescence properties of crystal samples. in the temperature range 77-500 K, will be presented. (C) 2004 Published by Elsevier B.V.